AS IT WAS IN THE BEGINNING, SO SHALL IT BE, WORLD WITHOUT END”RETRO-MARKETING: THE ART OF BRINGING BACK TO LIFE/REVITALIZING AN OLD BRAND (PRODUCT) – THE NIGERIAN EXPERIENCE - AYOZIE; OGECHUKWU, DANIEL (British Journal of Marketing Studies, 2014)
Retro-marketing revolution, revitalising, revivals, remakes, rejuvenating, returns, re-enactments, reissues and recreations are all around us in Nigeria and worldwide. From the simple wigs and high heel shoes worn by university, polytechnic, and college girls, to the re-launch of macleans close up appeal adverts. Retro and rejuvenating is one of the most pervasive marketing trends of our time. Branding is the process by which companies distinguish their product offerings from the competition. Doyle (1989). By developing a distinctive name, packaging, and design, a brand is created. Some brands are supported by logos. By developing an individual identity, branding permits customers to develop association with the brand, (e.g. prestige economy) and eases the purchase decision of the product. The American Marketing Association defines a brand as ‘a name, term, sign, symbol or design, or a combination of them intended to identify the goods or services of one seller or group of sellers as to differentiate them from those of competitors (AMA in Kotler, P. and Keller, K, 2010). A brand adds dimensions that differentiate the offering in some way from other offerings designed to satisfy the same need. These differences may be functional, rational or tangible, related to the brand’s product performance. They may also be more symbolic, emotional or intangible related to what the brand represents. (Kotler 2007). Brand encompass not only consumer goods, but other offerings such as people (e.g. politicians, pop-stars e.g. Michael Jackson, Sunny Ade), places (e.g. Nigeria, Lagos, South Africa, Durban), companies (e.g. Coca Cola, Nigerian Breweries), industrial products, services, products, etc. A brand is more than just the sum of its component parts. It embodies for the purchaser or user additional attributes which are intangible but real (deChernatony and McDonald 2006). This paper which is a literature review, conceptual reflection and research observation of some revitalised brands, products and services in Nigeria, it examines the rapid rise of Retro-marketing/Rejuvenating of old brands, it will explain the historical evolution of brands, the extend to which consumers search for brand information, issues associated with effective brand name and building successful brands. It will explain the demographic, socio-economic, cultural and organisational factors that have precipitated the latter day retro-rejuvenating outbreak in Nigeria. It will also look at how companies can manage brands. Why do companies rejuvenate? Rejuvenating “has been” brands is a systematic approach for revitalizing brands. It offers managerial causes and solutions on the best ways to revitalise old products. It concludes that retro/rejuvenating involves searching for authenticity in an inauthentic world, and present some basic factors that companies and managers bent on brand revival needs to consider